ax+cx=b
(a+c)x=b
x=b/(a+c)
2007-05-07 08:55:17
·
answer #1
·
answered by JO 3
·
0⤊
0⤋
ax+cx=b
(a+c)x=b
x=b/(a+c)
if a=-c the answer don't found
2007-05-07 16:10:11
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
ax=b-cx
ax+cx=b-cx+ax
x=b/a+c
2007-05-07 16:00:13
·
answer #3
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
ax=b-cx
ax+cx=b
x(a+c) = b
x= b/(a+c)
2007-05-07 15:58:47
·
answer #4
·
answered by ? 3
·
0⤊
0⤋
ax = b-cx
a=(b-cx)/x
a=b/x - cx/x
a=b/x - c
a+c=b/x
(a+c)/b = 1/x
b/(a+c)=x <<---flip both sides
2007-05-07 16:03:19
·
answer #5
·
answered by kirsty1995 2
·
0⤊
0⤋
How about get a tutor and stop trying to get freebie answers for your homework
2007-05-07 15:55:42
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
ax= b-cx
x= (b-cx) /a
2007-05-07 15:55:35
·
answer #7
·
answered by Scarlette 3
·
0⤊
0⤋
x=b(a+c)
2007-05-07 15:58:16
·
answer #8
·
answered by Tom S 1
·
0⤊
0⤋
b/a-c
2007-05-07 15:56:00
·
answer #9
·
answered by CHRISTOPHER C 4
·
0⤊
0⤋